Final Report : A National Discipline-specific Professional Development Program for Lecturers and Tutors in the Mathematical Sciences. - Vu, Tori (Australian Learning and Teaching Council (ALTC), 2011)
Australia has a distinct and increasingly urgent need for a formal professional development program for lecturers and tutors teaching in disciplines in the mathematical sciences, which count 18,000 undergraduate students yearly (DEEWR, 2008). Mathematics teaching staff receive some training in learning and teaching, but many of the courses run at university level are not tailored to the mathematical sciences. This is the final report from a project that aimed to explicitly embed the acquisition of teaching skills by developing a discipline-specific program of teacher development, and disseminating it through tertiary institutions across Australia. Higher degree by research and honours students were included in this project as these are our future academics and academic leaders. To ensure that this professional development is sustainable, it was attached to the Australian Mathematical Society annual conference, building capability as the conference moves around Australia each year.